Relationships between attitude, subjective norm and behavioural control with anti-littering intention among visitors to Shahid Zare Forest Park, Iran - Talooki, Kambiz Yousefi (2012)
At present, littering is the prevalent problem among Iranian forest parks. Forest parks’ managers made several efforts to overcome this undesirable problem. Unfortunately, the effectiveness of their approaches was restricted to short-term and to specific forest park, only because of neglecting a large number of underlying factors and beliefs. Many of the managers assumed such efforts to be efficient to obtain long term behavioural change in most forest parks. This study was conducted to determine the relationship between three fundamental variables, which are attitude, subjective norms, and perceived behavioural control with intention of forest parks’ visitors to perform anti-littering behaviour through utilizing theory of planned behaviour. Simple random sampling and convenience sampling were used in the survey. The sample of this study consisted of 382 forest parks’ visitors from the approximately total of 16000 of visitors who come to the Shahid Zare Forest Park during one month in peak session period. For the purpose of the wide coverage of sampling a total of 400 visitors who visited the park were surveyed in this research. Descriptive and inferential statistics were utilized to analyze the data collected. Pearson Correlation was used to answer the research questions. A significant level of 0.05 errors was used. Multiple linear regression were utilized to determine the contribution of the independent variables to predict dependent variables. The findings of the study revealed that the perceived behavioural control is the most effective variable (among three independent variables) to predict the visitors’ intention to perform active anti-littering behaviour followed by subjective norm and attitude as second and third predictor. On the other hand subjective norm was the first predictor to predict visitors’ intention to perform passive anti-littering behaviour followed by perceived behavioural control and attitude as second and third predictor. In general, it could be concluded that, TPB is an appropriate theory to predict intention of forest park’s visitors to perform anti-littering behaviour. Based on the finding of this study, it could be useful for forest parks’ manager to consider perceived behavioural control,subjective norm and attitude in their management approaches to obtain long term behavioural change among forest parks’ visitors.